Pengaruh Persepsi dan Minat Mahasiswa terhadap Motivasi Berkarir sebagai Guru - Erni Harlina Isdiati Erni; Arif Wahyu Wirawan; Muhammad Nukha Murtadlo (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of students’ perceptions and interests on their motivation to pursue a teaching career through the Teacher Professional Education Program (PPG). A quantitative approach was employed using a survey method. The population of this study consisted of final-year students from the Economics Education Study Program at Universitas Negeri Semarang, with a total sample of 200 students selected through purposive sampling based on criteria of understanding PPG and expressing interest in becoming teachers. The research instrument was a closed-ended questionnaire using a five-point Likert scale, which was tested for validity and reliability. Construct validity was examined through exploratory factor analysis (EFA), while reliability was measured using Cronbach’s Alpha with a threshold of α ≥ 0.70. Data analysis was conducted in two stages: descriptive analysis and inferential analysis using multiple linear regression. The results indicate that both students’ perceptions and interests have a positive and significant effect on their motivation to participate in the PPG and pursue a teaching career. These findings provide practical implications for the development of promotional strategies and educational policies to strengthen teacher professionalism in higher education institutions.